1999
DOI: 10.1002/ijch.199900041
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Excited‐State Proton Transfer and Geminate Recombination Processes in Water and in Glycerol‐Doped Ice

Abstract: The reversible proton dissociation and geminate recombination of photoacids was studied as a function of temperature in neat water, binary water mixture containing 0.6 mol% glycerol, and doped ice containing 0.6 mol% glycerol. The deuterium isotope effect on both condensed phases was also studied. 8‐hydroxypyrene‐1,3,6 trisulfonate trisodium salt was used as the electronically‐excited‐state proton emitter. The experimental data are analyzed by the Debye–Smoluchowski equation solved numerically with boundary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
1

Year Published

2001
2001
2005
2005

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(73 citation statements)
references
References 32 publications
6
66
1
Order By: Relevance
“…In previous studies, we used the longest component of the dielectric relaxation time, τ D , for the solvent-coordinate preexponential factor of the rate constant, k S = b /τ D exp(−Δ G ⧧ / RT ), where b is an empirical factor. For water, we found b ≈ 6 and, for all monols studied, the value is less, 2 < b < 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we used the longest component of the dielectric relaxation time, τ D , for the solvent-coordinate preexponential factor of the rate constant, k S = b /τ D exp(−Δ G ⧧ / RT ), where b is an empirical factor. For water, we found b ≈ 6 and, for all monols studied, the value is less, 2 < b < 4.…”
Section: Discussionmentioning
confidence: 99%
“…Excited-state proton transfer (ESPT) from a photoacid molecule was used in studies of proton-transfer reactions in liquids and solids. Recent studies on the proton-transfer rate to the solvent emphasize the dual role played by the solvent molecule (1) as a proton acceptor and (2) as a solvating medium of both the reactant and the product. …”
Section: Introductionmentioning
confidence: 99%
“…The solvent velocity, Ṡ , on the other hand, strongly depends on the temperature. In our previous papers, we suggested that Ṡ is related to the slow components of the solvent dielectric relaxation. We infer that Ṡ = b /τ D , where τ D is the solvent dielectric relaxation time and b is an empirical factor, dependent on the specific protic solvent, and its value is between 1 and 4 for the proton-transfer reaction from a photoacid to several alcohols.…”
Section: Modeling Of the Proton Abnormal Conductivitymentioning
confidence: 96%
“…Also we found that the inverse of the proton-transfer rate constant at low temperature has a value similar to τ D . Previously, we found that the temperature dependence of the proton-transfer rate constant from several photoacids to solvent is explained as a continuous transition from nonadiabatic to solvent-controlled limits. In the nonadiabatic limit, the rate-determining step in the proton-transfer rate is the proton tunneling from the proton donor (the acid) to the proton acceptor (a hydrogen-bonded solvent molecule).…”
Section: Introductionmentioning
confidence: 94%
“…In this picture the excited state proton transfer dynamics, controlled by barrier crossing, is described by a two-state model (Figure 1 a), where an optically excited photoacid state converts into an excited conjugated photobase upon proton transfer. [16][17][18][19][20][21][22][23][24][25][26] A second model invokes the occurrence of and the internal conversion between nearby lying electronic excited levels of the photoacid (Figure 1 b). Typically two spectroscopically accessible states can be reached for aromatic molecules upon electronic excitation, either with light polarized along the through-bond axis ( 1 L b state) or along the through-atom axis…”
Section: Introductionmentioning
confidence: 99%